Answer:
Solution:
Given that,
x⁴y⁵ + x⁵y⁴ = 810
➝ x⁴y⁴(x+y) = 810 ---(1)
Further given that,
x⁶y³ + x³y⁶ = 945
x³y³(x³y³) = 945
We know,
So, using this identity, we get,
➝ x³y³( x + y )( x² - xy + y²) = 945
---(2)
On dividing equation (1) and (2), we get,
➝ 6x² + 6y² = 13xy
➝ 6x² - 13xy + 6y² = 0
➝ 6x² - 4xy - 9xy + 6y² = 0
➝ 2x( 3x - 2y ) - 3y( 3x - 2y ) = 0
➝ ( 3x - 2y ) ( 2x - 3y ) = 0
In Substating the value of x in equation (1) we get,
On Substituting the value of y in equation (2), we get,